The Marxian influence on Leonard Woolf's theory of imperialism. (September 2019) - Villanueva, Ricardo
In his own time, Leonard Woolf was one of the most prolific and respected experts on international affairs. Yet, his paramount place in the field fell rapidly, partly because he was a writer whose ideas have been labelled as utopian. This article employs Woolf to challenge the orthodox narrative of the discipline of International Relations (IR) that oversimplifies the early stages of the field as a dichotomy between idealism and realism. While this has already been done cogently by Peter Wilson, this article discloses a Marxist dimension in Woolf's thought and writings. This is particularly important given that Marxism has regained significance in recent IR debates. Through a contextualist approach, this article demonstrates that Woolf represents a considerable challenge to conventional IR historiography and reveals the significance of Marxian-based understandings in the early stages of the discipline as an alternative to idealism and realism. In addition, this article shows some of the distinctiveness in Woolf's Marxian writings on imperialism as an alternative to Leninist understandings.